2007
DOI: 10.1364/josab.24.001535
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of infrared photorefractive properties of Sn_2P_2S_6 crystals by Te and Sb doping

Abstract: The photorefractive properties of Sn 2 P 2 S 6 crystals doped with Te and Sb in the near-infrared wavelength range up to 1064 nm are reported. The main photorefractive parameters, i.e., two-wave mixing gain, effective electrooptic coefficient, diffusion length, concentration of traps, and response time, are compared with conventional nominally pure Sn 2 P 2 S 6 . Te-doped Sn 2 P 2 S 6 shows the fastest response with the smallest decrease of the photorefractive efficiency with increasing wavelength in the near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] Specific dopants, such as Sb, Te, and Bi, are known to significantly affect the wavelength response and the speed of the photorefractive effect in the Sn 2 P 2 S 6 crystals. [14][15][16][17][18][19] Doping with Sb ions introduces a near-edge optical absorption band that shifts the onset of transparency to longer wavelengths (from about 530 nm for an undoped crystal to near 650 nm when the Sb doping level is 2%). 18 A significant increase in the photorefractive gain factor for red light correlates with the presence of this Sb-related optical absorption band and its associated photoconductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] Specific dopants, such as Sb, Te, and Bi, are known to significantly affect the wavelength response and the speed of the photorefractive effect in the Sn 2 P 2 S 6 crystals. [14][15][16][17][18][19] Doping with Sb ions introduces a near-edge optical absorption band that shifts the onset of transparency to longer wavelengths (from about 530 nm for an undoped crystal to near 650 nm when the Sb doping level is 2%). 18 A significant increase in the photorefractive gain factor for red light correlates with the presence of this Sb-related optical absorption band and its associated photoconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…18 A significant increase in the photorefractive gain factor for red light correlates with the presence of this Sb-related optical absorption band and its associated photoconductivity. 15,18 More recently, preilluminated Sb-doped crystals have been shown to contain secondary photorefractive centers that affect the dynamics of the beam coupling and cause transient beam fanning. 20 Until the present study, no candidates for these Sb-related secondary centers have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, this technique has the disadvantage of being relatively slow, to the point of becoming impractical for use with living biological tissue: the typical response time of a PRC based system is 10-100 ms. 7,8 In contrast, the decorrelation time in biological tissue is less than 0.1 ms. 9 Recently, techniques based on cryogenically cooled rare-earth-ion-doped crystals have received some interest due to the ability to create high contrast spectral filters using spectral hole burning. 10 In particular, this is highly effective in Pr 3þ : Y 2 SiO 5 due to the long spectral hole lifetime.…”
mentioning
confidence: 98%
“…The fast response time, high gain factor, and broad spectral sensitivity, which is extended for some dopants up to telecommunication wavelength 1.5 m μ , make Tin Hypothiodiphosphate (Sn 2 P 2 S 6 , SPS) an attractive photorefractive material for numerous applications [1][2][3][4]. At the same time, the photorefractive response of SPS is still inhibited by the space charge field limitation, a consequence of the insufficient effective trap density [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the photorefractive response of SPS is still inhibited by the space charge field limitation, a consequence of the insufficient effective trap density [5]. In part, the problem of insufficient effective trap density was solved by technological efforts: crystals deliberately doped during the growth procedure showed improved characteristics [3,6,7]. There remains, however, still much room for further improvement, until the fundamental limit for the gain factor is reached, which is defined by the largest Pockels tensor component of SPS.…”
Section: Introductionmentioning
confidence: 99%